Current-Voltage Characterization on Au-DNA-Au Junctions under the Influence of Magnetic Field - Mahmoudy Khatir, N.; Banihashemian, S.M.; Periasamy, V.; Abd Majid, Wan Haliza; Abdul Rahman, S. (2012)
We utilized Deoxyribonucleic acid (DNA) strands immobilized between a metal gap and its behavior was investigated. The DNA strands were initially prepared using the PCR method while gaps of 10.00 Î¼m lengths were created on gold layer deposited onto silicon substrate. Once immobilized, current-voltage characterization was carried out on the Au-DNA-Au structure fabricated under the presence and absence of magnetic field. Experimental results clearly highlight the behavior of the DNA strands similar to semiconductor materials. An exponential decrease observed in the current in presence of external magnetic field suggests possible future application as a magnetic sensor.